التحكيم بين الزوجين في قانون الأحوال الشخصية الإماراتي 2005م : دراسة تحليلية - صبحي، عبد العزيز عبد الله سعيد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
Arbitration between spouses is an old mechanism to resolve the discord between them. Islam has approved and systemized it, which resulted in many rulings and issues that need to be examined and studied. United Arab Emirates (UAE) legislators have approved that mechanism with a set of legal provisions that lack scrutiny and analysis. Actually, jurists have unanimously agreed on its legality, but they disagreed on the nature of the two arbitrators: are they two judges or two representatives? Therefore, that has affected a number of provisions. UAE legislators have considered both arbitrators as two judges. Hence, this has increased the importance of this mechanism in UAE community as it is one of the most important mechanisms dealing with family reconciliation. Likewise, it has a significant impact on reducing the percentage of divorce and as well as the burden of judiciary. This study has four objectives, which are summarized as follows: firstly, discussion on the importance and status of arbitration, and its impact on family and judiciary reform. Secondly, a comparative study of the jurisprudential provisions concerning arbitration between spouses, with a highlight on the most correct provision. Thirdly, a study of the legal provisions regarding the organization of arbitration between spouses in the UAE Personal Status Law in the light of the most correct opinions of the jurists. Fourthly, analysis of the survey to show the quality of arbitration between spouses. The researcher has adopted several methodologies in this thesis, which are inductive, survey, analytical and critical ones. As for the inductive and analytical methodologies, the researcher has used them to collect legal texts regarding the Personal Status Law, texts of the provisions of the reversal from different courts to which they belong and analysis and discussion of the most correct view on the jurisprudential issues from the Islamic jurisprudential books. The researcher has given special attention to Shari‛ah terms in order to reach a precise description of the themes studied such as the definition of al-Nushuz, al-Shiqaq and al-Taḥkim. A critical approach is adopted in the discussion of the articles and legal texts in the light of the most correct opinions of the jurists. The researcher has adopted the last method, which is the survey and the related questionnaire, to determine the quality of the arbitration and its proximity to the Shari‛ah and legal texts. Among the most important findings of the research is that the most correct view is to consider the two arbitrators as two judges, not two representatives. The two arbitrators are not required to possess the whole qualities of a judge. The most important objective of the Shari‛ah which must be attained is the principle of bringing benefit and preventing evil. In the Personal Status Law, the two arbitrators are not permitted to enforce divorce if reconciliation is not possible. Indeed, that will negatively affect society. In fact, there is a need to educate, train and rehabilitate the arbitrators theoretically and practically. However, to achieve good results, the two arbitrators should come from the location of the spouses themselves.